The Effectiveness of Hypnobreast feeding Massage on Anxiety and Breast Milk Production in Postpartum Mothers. - Septianingrum, Yurike; Hatmanti, Nety Mawarda; Fitriasari, Andikawati; Wijayanti, Lono; Purwanti, Nunik (Gaceta Médica de Caracas, 2022)
Low milk production on the first day after delivery causes the mother to experience anxiety, which increases the hormone cortisol. When the hormone cortisol level is high, milk production will be hampered, resulting in an early stop of the breastfeeding process. This study aimed to analyze the effectiveness of Hypno-breastfeeding massage on anxiety and milk production in postpartum mothers at the Public Health Center.